Ab Initio Simulations of the (101) Surfaces of Potassium Dihydrogenphosphate (KDP) - Carter, Damien; Rohl, Andrew; Gale, Julian (American Chemical Society, 2006)
We have used density functional calculations to examine the (101) surfaces of KDP, under vacuum, nitrogen, and aqueous conditions, and these simulations are found to agree well with nanoscale experimental studies demonstrating that the density functional calculations are providing a good description of the surfaces of this complex inorganic salt.